Quantification of the compaction problem of selected vineyard soils and a critical assessment of methods to predict soil bulk density from soil texture - Van Huyssteen, Leopoldt (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhDAgric)--Stellenbosch University, 1989.